Progress in fungal polyketide biosynthesis - Chen, Xiwei; Xu, Meng; Feng, Cheng; Hu, Changhua (Shengwu gongcheng xuebao, 2018)
Fungal polyketides display complex structures and variously biological activities. Their biosynthetic pathways generally contain novel enzyme-catalyzed reactions. This review provides a summary of recent research advances in molecular mechanism of the biosynthesis of fungal polyketides including highly-reducing polyketide synthases (HR-PKSs), non-reducing polyketide synthases (NR-PKSs), as well as polyketide-nonribosomal peptide synthase (PKS-NRPSs) and reducingnon- reducing polyketide synthase (HR-NR PKSs) hybrids. The elucidation of biosynthetic mechanism of many fungal polyketides provides guidance on the discovery of new biosynthetic gene cluster of fungal polyketide natural products and compounds with novel structures as well as their analogue.